Big data service investment choices in a manufacturer-led dual-channel supply chain. (September 2022) - Song, Han; Shu, Yuxin; Dai, Ying; Zhou, Lin; Li, Haiyan
Highlights: Examine impact of big data service investment on a dual-channel supply chain. The impact of the manufacturer and the retailer's big data service investment on the supply chain is studied, respectively. Study the difference between the impact of big data service on two channels at the same time and only one channel. Whether the manufacturer and the retailer choose the same model depends on the fixed cost value. Cost sharing contract can coordinate supply chain and improve big data service level. Abstract: This paper investigates the impact of different supply chain members invest in big data service on profits by developing game-theoretic models for a dual-channel supply chain consisting of one manufacturer and one retailer. We consider the difference between big data service impacting both channels and impacting only one (traditional retail channel or online direct marketing channel). The results show that whether the manufacturer or the retailer invests in big data service, the impact of big data service on two channels at the same time is more attractive to the manufacturer and the retailer than just one channel. There are three models of investing in big data services that only affect a single channel, resulting in unreasonable pricing decisions and big data service level. In the other three models, when the fixed cost of big data service investment is large, the manufacturer and the retailer are reluctant to invest in big data service. When the investment cost is small, both parties are willing to invest in big data service. This will lead to the manufacturer and retailer making different choices, and the manufacturer as the leader will adopt the cost-sharing strategy to motivate the retailer to agree to choose the same model with the manufacturer. However, when the investment cost of big data services is moderate, the manufacturer and the retailer will choose the manufacturer to invest in big data service. Moreover, the manufacturer and the retailer will not choose the model where the manufacturer invests in big data service only affect the online direct marketing channel, because this model cannot maximize profit of them. Finally, according to the conclusion, management suggestions and enlightenment are obtained.